2017
DOI: 10.1016/j.jpsychires.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Does the increasing placebo response impact outcomes of adult and pediatric ADHD clinical trials? Data from the US Food and Drug Administration 2000–2009

Abstract: In a study of recent antidepressant clinical trial data, it was found placebo response had grown significantly over time and that contrary to expectations, trial outcome measures and success rate were not impacted. The aim of this paper was to evaluate if this trend of increasing placebo response and stable outcome measures could be seen in clinical trial data for Attention-Deficit Hyperactivity Disorder, a different psychiatric condition with susceptibility to placebo response. For this reason, we evaluated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
3
20
0
Order By: Relevance
“…These source-verified and independently reviewed data confirm previous suggestions of a rising placebo response from analyses of published studies [2][3][4] and further support the findings from previous researchers that AED efficacy has not changed significantly over the years [8,9]. This constellation of effects appears to be a general phenomenon across clinical trials for disorders of various types, as this pattern of rising placebo and stable outcomes has been seen in psychiatric [10,11] and non-psychiatric conditions.…”
Section: Discussionsupporting
confidence: 81%
“…These source-verified and independently reviewed data confirm previous suggestions of a rising placebo response from analyses of published studies [2][3][4] and further support the findings from previous researchers that AED efficacy has not changed significantly over the years [8,9]. This constellation of effects appears to be a general phenomenon across clinical trials for disorders of various types, as this pattern of rising placebo and stable outcomes has been seen in psychiatric [10,11] and non-psychiatric conditions.…”
Section: Discussionsupporting
confidence: 81%
“…In support of our hypothesis, both sets of analysis of treatment arms from the two common types of placebo-controlled trial design (exclusively placebo-controlled and augmented placebo-controlled) demonstrated that there is a nontrivial placebo response in clinical trials for type 2 diabetes. Similar to the apparent generalized phenomenon seen in trials of other psychiatric and physical conditions (5)(6)(7)(8), the magnitude of placebo response is rising significantly over time, whereas effect sizes and success rates have remained unaffected.…”
Section: Discussionmentioning
confidence: 56%
“…This pattern of a rising placebo response and stable outcome measures is similar to the pattern seen in other chronic illnesses, supporting the assumption that this pattern may represent a generalized phenomenon across placebocontrolled clinical trials. As in the case of antidepressants (5), attention-deficit hyperactivity disorder medications (6), antihypertensives, and antiepileptics (7,8), the significant growth in placebo response in both exclusive and augmented placebo-controlled trials of type 2 diabetes appears not to have had an effect on trial efficacy outcomes. Like other medication trials, this lack of effect on efficacy outcomes appears to be related to the apparent, although not statistically significant, proportional increase in drug response over time ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect size, drug-placebo differences, and success rate have remained stable, due to a parallel increase in drug response. This pattern of rising placebo response and unaffected trial outcomes does not appear to be unique to antidepressant trials; we have also seen it in clinical trials for ADHD medications [ 5 ], antiepileptics [ 6 ], and antihyperglycemics [ 7 ].…”
Section: Introductionmentioning
confidence: 99%